Residential Mobility Fosters Sensitivity to the Disappearance of Happiness. (9th October 2019) - Ishii, Keiko; Komiya, Asuka; Oishi, Shigehiro
Abstract : We conducted two studies to examine the hypothesis that residential mobility would evoke anxiety and foster sensitivity to signs of disapproval, such as the disappearance of happiness. American and Japanese participants were asked to watch happy‐to‐neutral movies and sad‐to‐neutral movies and judge the point at which they thought that their initial expressions had disappeared. We found that, regardless of cultures, participants who had experienced frequent moving (Study 1) and those asked to imagine and describe a mobile lifestyle of frequent moving (Study 2) judged the disappearance of happy faces faster than those who did not experience or imagine frequent moving. Our results were also in line with the previous finding in which Japanese were more vigilant than Americans in regards to the disappearance of happy faces. Moreover, we found that imagining a mobile lifestyle made participants feel more concerned than when imagining a stable lifestyle. The implications for the social skills needed for people in the globalising world are discussed.